The Influence of Transformational Leadership on the Performance of Healthcare Workers in Hospitals: Literature Review - Ismail; Lintang Dyah Ayu Pangukir (Penerbit Hellow Pustaka, 2026)
The quality of hospital services is largely determined by the performance of healthcare workers, which is influenced by various managerial factors, one of which is transformational leadership. This study aims to examine the influence of transformational leadership on healthcare worker performance in hospitals through a literature review approach. The method used was a narrative literature review, with a search of scientific articles from the Google Scholar, PubMed, MDPI, and ScienceDirect databases. The articles analyzed were published in the last five years (2020–2024) that were relevant to the research topic and available in full text. The results of the review of ten articles indicate that transformational leadership consistently has a positive influence on healthcare worker performance, reflected in increased work motivation, job satisfaction, psychological safety, Organizational Citizenship Behavior (OCB), team collaboration, and improved hospital service quality. Based on these results, it can be concluded that transformational leadership is a crucial factor in improving healthcare worker performance and contributes to improving the overall quality of healthcare services in hospitals.